Daughter of no worlds - Broadbent, Carissa (Broadbent, Carissa, War of lost hearts, 2025)
"A former slave fighting for justice. A reclusive warrior who no longer believes it exists. And a dark magic that will entangle their fates....fans of romantic fantasy will devour this tale from New York Times bestselling author Carissa Broadbent. Ripped from a forgotten homeland as a child, Tisaanah learned how to survive with nothing but a sharp wit and a touch of magic. But the night she tries to buy her freedom, she barely escapes with her life. Desperate to save the best friend she left behind, Tisaanah journeys to the Orders, the most powerful organizations of magic Wielders in the world. To join their ranks, she must complete an apprenticeship with Maxantarius Farlione, a handsome and reclusive fire wielder who despises the Orders. The Orders' intentions are cryptic, and Tisaanah must prove herself under the threat of looming war. But even more dangerous are her growing feelings for Maxantarius. The bloody past he wants to forget may be the key to her future... or the downfall of them both. Tisaanah will stop at nothing to save those she abandoned. Even if it means gambling in the Orders' deadly games. Even if it means sacrificing her heart. Even if it means wielding death itself. This is the first book in the new War of Lost Hearts series"-- Provided by publisher.